Photodynamic therapy in brain cancer: mechanisms, clinical and preclinical studies and therapeutic challenges - Domka, Wojciech; Bartusik-Aebisher, Dorota; Rudy, Izabela; Dynarowicz, Klaudia; Pięta, Karolina; Aebisher, David (Frontiers in Chemistry, 2023)
Cancer is a main cause of death and preferred methods of therapy depend on the type of tumor and its location. Gliomas are the most common primary intracranial tumor, accounting for 81% of malignant brain tumors. Although relatively rare, they cause significant mortality. Traditional methods include surgery, radiotherapy and chemotherapy; they also have significant associat-ed side effects that cause difficulties related to tumor excision and recurrence. Photodynamic therapy has potentially fewer side effects, less toxicity, and is a more selective treatment, and is thus attracting increasing interest as an advanced therapeutic strat-egy. Photodynamic treatment of malignant glioma is considered to be a promising additional therapeutic option that is current-ly being extensively investigated in vitro and in vivo. This review describes the application of photodynamic therapy for treat-ment of brain cancer. The mechanism of photodynamic action is also described in this work as it applies to treatment of brain cancers such as glioblastoma multiforme. The pros and cons of photodynamic therapy for brain cancer are also discussed.